Geometric Regularization in Bioluminescence Tomography - Kreutzmann, Tim (KIT Scientific Publishing, 2014)
Bioluminescence tomography is a recent biomedical imaging technique which allows to study molecular and cellular activities in vivo. From a mathematical point of view, it is an ill-posed inverse source problem: the location and the intensity of a photon source inside an organism have to be determined, given the photon count on the organism's surface. To face the ill-posedness of this problem, a geometric regularization approach is introduced, analyzed and numerically verified in this book.